2022
DOI: 10.5306/wjco.v13.i11.918
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of texture analysis of pre-operative magnetic resonance imaging in predicting microvascular invasion in hepatocellular carcinoma

Abstract: BACKGROUND Presence of microvascular invasion (MVI) indicates poorer prognosis post-curative resection of hepatocellular carcinoma (HCC), with an increased chance of tumour recurrence. By present standards, MVI can only be diagnosed post-operatively on histopathology. Texture analysis potentially allows identification of patients who are considered ‘high risk’ through analysis of pre-operative magnetic resonance imaging (MRI) studies. This will allow for better patient selection, improved individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Calculating parametric feature maps might have been beneficial in their study since variance, skewness, kurtosis, and entropy showed increased reproducibility across VOI sizes when extracted from the feature maps (yet, mean is also reproducible when derived conventionally from the original images). Another group [ 40 ] analyzed links between textural features and microvascular invasion in hepatocellular carcinoma in post-contrast-enhanced T1-weighted images. Resected specimens served as the reference standard.…”
Section: Discussionmentioning
confidence: 99%
“…Calculating parametric feature maps might have been beneficial in their study since variance, skewness, kurtosis, and entropy showed increased reproducibility across VOI sizes when extracted from the feature maps (yet, mean is also reproducible when derived conventionally from the original images). Another group [ 40 ] analyzed links between textural features and microvascular invasion in hepatocellular carcinoma in post-contrast-enhanced T1-weighted images. Resected specimens served as the reference standard.…”
Section: Discussionmentioning
confidence: 99%
“…Xiong et al [ 37 ] developed a prediction model based on preoperative AFP, tumor diameter, and TNM stage with an area under the receiver operating characteristic curve of 0.80 and good practicability. Texture analysis of tumor nodules could improve the diagnosis of MVI over visual analysis by human readers [ 38 ] and harbors the potential for deep learning algorithm development. Unfortunately, owing to the numerous types of image features, most studies have used different classification features and weights to predict MVI.…”
Section: Imaging Features Of MVImentioning
confidence: 99%
“…Occasionally, literature has demonstrated that high cell proliferation index KI-67 [9], mutation of tumor suppressor gene P53 [10] and other factors are correlated with poor prognosis. In addition, incomplete tumor capsule [11], MVI [12,13], envelope invasion (EI) [14], vascular invasion (VI) and SN [15,16] often represent poor prognosis. However, the thickness of hepatic plates (HP), vessels encapsulating tumor clusters (VETC) [17] and some other novel biomarkers, which were recently found to correlate with prognosis and/or treatment, were seldomly included in the pathological diagnosis report.…”
Section: Introductionmentioning
confidence: 99%